Cancer-Selective Induction of Apoptosis by Leczyme - Tatsuta, Takeo; Sugawara, Shigeki; Takahashi, Kohta; Ogawa, Yukiko; Hosono, Masahiro; Nitta, Kazuo (Frontiers in Oncology, 2014)
Sialic acid-binding lectin (SBL) is a multifunctional protein that is isolated from oocytes of Rana catesbeiana. It has both lectin and ribonuclease (enzyme) properties, and therefore is called leczyme. We examined the antitumor effects of SBL and discovered that SBL has potential as a new type of anticancer drug. SBL causes a cancer-selective induction of apoptosis by multiple signaling pathways whereby RNA is its target. It is suggested that the mitochondrial pathway and endoplasmic reticulum stress-mediated pathway participate in SBL-induced signaling. The synergistic antitumor effects with other molecules, such as tumor necrosis factor-related apoptosis ligand (TRAIL) and interferon γ (IFN-γ), have been reported. In this study, we summarize the effects of SBL and focus on its cancer-selective apoptotic properties. In addition, we present a possible explanation its cancer specificity.